Megengan as a Javanese Islamic Tradition to Welcome the Holy Month of Ramadhan in The Community of Bangunrejo Kidul Kedunggalar Ngawi Village - Fatimah, Siti; Masamah, Ulfa; Choiriyah, Isti (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
The megengan tradition in Bangunrejo Kidul Kedunggalar Ngawi Village has become a habit that is still maintained to this day. The megengan tradition is a form of greeting accompanied by joint prayer activities. Megengan is a concrete form of acculturation between Javanese culture and Islamic religious teachings. Megengan can mean holding back, in the context of the month of Ramadan, this tradition means holding back desires related to eating, drinking, sexual relations, and so on. The megengan tradition can be a marker for Muslims to make special preparations before the arrival of the holy month of Ramadan. Megengan, from an Islamic perspective, has several religious values. Megengan is a means of da'wah and a means of broadcasting the Islamic religion. Megengan is also a symbol of gratitude to Allah SWT, who still provides the opportunity to meet the holy month of Ramadan. Megengan is also a means of strengthening ties between Hamlet residents, with the gathering of residents in one place creating an opportunity for residents to strengthen each other's harmony.